Life cycle assessment of ethanol production from miscanthus: A comparison of production pathways at two European sites. Issue 1 (2nd September 2018) - Lask, Jan; Wagner, Moritz; Trindade, Luisa M.; Lewandowski, Iris
Abstract: Lignocellulosic ethanol represents a renewable alternative to petrol. Miscanthus, a perennial plant that grows on marginal land, is characterized by efficient use of resources and is considered a promising source of lignocellulosic biomass. A life cycle assessment (LCA) was performed to determine the environmental impacts of ethanol production from miscanthus grown on marginal land in Great Britain (Aberystwyth) and an average‐yield site in Germany (Stuttgart; functional unit: 1 GJ). As the conversion process has substantial influence on the overall environmental performance, the comparison examined three pretreatment options for miscanthus. Overall, results indicate lower impacts for the production in Stuttgart in comparison with the corresponding pathways in Aberystwyth across the analysed categories. Disparities between the sites were mainly attributed to differences in biomass yield. When comparing the conversion options, liquid hot water treatment resulted in the lowest impacts, followed by dilute sulphuric acid. Dilute sodium hydroxide pretreatment represented the least favourable option. Site‐dependent variation in biomass composition and degradability did not have substantial influence on the environmental performance of the analysed pathways. Additionally, implications of replacing petrol with miscanthus ethanol were examined. Ethanol derived from miscanthus resulted in lower impacts with respect to greenhouse gas emissions, fossil resource depletion, natural land transformation and ozone depletion. However, for other categories, including toxicity, eutrophication and agricultural land occupation, net scores were substantially higher than for the fossil reference. Nevertheless, the results indicate that miscanthus ethanol produced via dilute acid and liquid hot water treatment at the site in Stuttgart has the potential to comply with the requirements of the European Renewable energy directive for greenhouse gas emission reduction. For ethanol production at the marginal site, carbon sequestration needs to be considered in order to meet the requirements for greenhouse gas mitigation. Abstract : Lignocellulosic ethanol represents a renewable alternative to petrol. Miscanthus, a perennial plant, is characterised by efficient resource use and is considered a promising source of lignocellulosic biomass. A LCA was performed to compare the environmental impacts of ethanol production from miscanthus grown on marginal land and an average‐yield site. In addition, three pretreatment options for miscanthus were compared. Results indicate lower impacts for the production at the average site, with the disparities mainly attributable to differences in biomass yield. Irrespective of the site, liquid hot water treatment has shown to be the pretreatment option with the lowest impacts overall.